Faktor –Faktor yang Mempengaruhi Pembiayaan Mudharabah pada Bank Umum Syariah di Indonesia - Rifqi Khuamirotun Nafis; Heri Sudarsono (ITB AAS INDONESIA Surakarta, 2021)
In general sharia banking in Indonesia, there are various types of financing offered to customers, one of which is profit-sharing based financing (Mudharabah). Regarding this, the purpose of this study is to determine and measure the relationship between positive and negative and significant or insignificant effects of micro independent variables in the form of TPF, CAR, NPF, FDR, BOPO and macro independent variables in the form of BI Rate and Inflation on the dependent variable, namely PMD. (Mudaraba Financing). In this study using the ARDL (Auto-regression Distributed Lag) regression method with analysis tools, namely the EViews 10 application and for the data used is time series data, the data is also secondary data which is retrieved from the official website of the OJK and BPS Indonesia by retrieving data. from January 2015 - July 2020. It can be concluded that the results of this study show that the independent variables have an effect on micro, namely TPF, CAR, ROA, and BOPO, the results have a negative and significant effect, while the NPF and FDR results are not significant (no influential) and for the independent variable the macro effect is the Bi Rate, the results have a significant negative effect, while for the inflation the results are positive and insignificant (no effect) on PMD (Mudharabah Financing).